2013
DOI: 10.1111/ens.12037
|View full text |Cite
|
Sign up to set email alerts
|

Vicariant speciation due to 1.55 Ma isolation of theRyukyu islands,Japan, based on geological andGenBank data

Abstract: The Ryukyu island arc, originally a continental margin arc, separated from the Chinese continent by the rifting of the Okinawa trough, a process which began at 1.55 million years ago (Ma) and continues to the present. In addition, the Ryukyu arc was simultaneously divided into the northern Amami-Okinawa and southern Yaeyama islands by the Kerama rift valley, and consequently formed two isolated island units. The Kuroshio warm current began to flow into the Okinawa trough from the Yonaguni Strait, and flow out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 21 publications
(55 reference statements)
2
22
0
Order By: Relevance
“…Phylogenetic reconstruction of insects also provided an implication for the timing of the isolation of the islands as in the form of group. It is estimated that Amami-Okinawa, Yaeyama and Taiwan were likely to be branched simultaneously around 1.55 Ma (Osozawa et al 2013). Although the detailed context of events and their localities may still require further investigations, the ongoing tectonics in the Okinawa Trough can be well understood within the framework of a developing Quaternary back-arc basin.…”
Section: Origin and Evolutionmentioning
confidence: 99%
“…Phylogenetic reconstruction of insects also provided an implication for the timing of the isolation of the islands as in the form of group. It is estimated that Amami-Okinawa, Yaeyama and Taiwan were likely to be branched simultaneously around 1.55 Ma (Osozawa et al 2013). Although the detailed context of events and their localities may still require further investigations, the ongoing tectonics in the Okinawa Trough can be well understood within the framework of a developing Quaternary back-arc basin.…”
Section: Origin and Evolutionmentioning
confidence: 99%
“…1), could not affect genetic structure of T. stimpsonii, although many studies have reported that faunal or genetic similarities are distinctively small between the northern and southern areas of the Tokara Gap (e.g., Ota, 1998;Osozawa et al, 2013). Results of demographic analyses (Tajima's D, Fu's Fs, and mismatch distribution) for Lineages 1-main, 1-sub, and 2 suggested that populations of these lineages have experienced sudden expansions.…”
Section: Genetic Diversity and Distributional History Of T Stimpsoniimentioning
confidence: 94%
“…Studies on vertebrates and insects with flying ability have revealed that the geological events in the Pleistocene drove speciation and/or intraspecific diversification of animals (e.g., Motokawa, 2000;Ota, 2000a;Osozawa et al, 2013). However, an ancestor of Diplothrix legata, a rodent endemic to Okinawajima, Tokunoshima and Amamioshima Islands of the Central Ryukyus, is estimated to have separated from allied lineages at the beginning of the Pleistocene, while the divergence time of the genus Tokudaia (an endemic rodent to these islands) is postulated to be rather earlier, 14-40 Mya (Suzuki et al, 2000).…”
Section: Diversification Of T Stimpsonii and T Crucifer Between Thementioning
confidence: 99%
See 1 more Smart Citation
“…Osozawa et al . () showed evidence for allopatric speciation of Ryukyu Pyrocoelia using GenBank/DDBJ data, and used 1.55 Ma as the calibration point. However, the sequence data comprised c .…”
Section: Introductionmentioning
confidence: 99%